Analysis of Teachers’ Difficulties in Implementing the Pancasila Student Profile Strengthening Project (P5) with the Theme Bhinneka Tunggal Ika through the Art Performance of Grade V Students at SD IT Nurul Iman Palembang - Kiftiah, Maryatul; Nuralaeli; Al Ihwanah; Mardiah Astuti; Siti Fatimah (TOFEDU: The Future of Education Journal, 2025)
The objective of this study is to analyze the challenges faced by teachers as well as the strategies used to overcome them. This research employs a qualitative descriptive approach with participants consisting of the school principal, homeroom teachers, and students selected through purposive sampling. Data collection techniques include structured interviews, non-participant observations, and documentation, while data analysis follows the interactive model of Miles and Huberman. The findings indicate that teachers experience significant obstacles in the planning, implementation, and evaluation of the P5 program, particularly in determining performance concepts, managing time, and preparing costumes and properties. The study highlights that collaboration among teachers, school leaders, and parents, along with the use of simple materials, is effective in addressing these challenges. The conclusion asserts that the implementation of P5 strengthens students’ character and awareness of diversity; however, further research is needed to generalize the findings and explore the role of technology in project-based learning.